2019
DOI: 10.15171/ijoem.2019.1610
|View full text |Cite
|
Sign up to set email alerts
|

A Study into Psychosocial Work Stressors and Health Care Productivity

Abstract: Background: World Health Organization's Healthy Workplace Framework and Model has emphasized addressing psychosocial work stressors as one of the important avenues toward creating a conducive workplace. Management and interventions of these adverse stressors have been unremarkable; impairing work productivity. Objective: To explore the effect of psychosocial work stressors on health service productivity. Methods: Using Copenhagen Psychosocial Questionnaire II and Healthcare Productivity Survey, a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
3
0
5
Order By: Relevance
“…Un estudio realizado por Lu et al 28 en 2 299 profesionales, 2 042 médicos y 257 administrativos hospitalarios durante la pandemia COVID-19 señaló que los primeros tuvieron más presencia de temor, así como ansiedad y depresión cuando se midieron con la escala de ansiedad de Hamilton [HAMA] y la escala de depresión de Hamilton [HAMD]. A las condiciones laborales que usualmente incluyen numerosas horas continuas de actividad profesional, se suman pensamientos, percepciones, sentimientos y actuaciones que se convierten en estresores, que contribuyen a deteriorar el bienestar emocional, social y la productividad [29][30][31][32][33][34] .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Un estudio realizado por Lu et al 28 en 2 299 profesionales, 2 042 médicos y 257 administrativos hospitalarios durante la pandemia COVID-19 señaló que los primeros tuvieron más presencia de temor, así como ansiedad y depresión cuando se midieron con la escala de ansiedad de Hamilton [HAMA] y la escala de depresión de Hamilton [HAMD]. A las condiciones laborales que usualmente incluyen numerosas horas continuas de actividad profesional, se suman pensamientos, percepciones, sentimientos y actuaciones que se convierten en estresores, que contribuyen a deteriorar el bienestar emocional, social y la productividad [29][30][31][32][33][34] .…”
Section: Discussionunclassified
“…La ansiedad es un estado fisiológico que responde a mecanismos neuroendocrinos y aflora cuando el organismo está bajo condiciones de riesgo o desventaja 30,34 En el estudio observamos que el 38 % de los participantes presentaron ansiedad, algo menor a lo observado en un estudio realizado por Lai et al 16 también bajo la pandemia COVID-19 en la provincia de Hubei y ciudad de Wuhan, donde encontraron 44,6%. El común denominador que eleva la presencia de ansiedad en los profesionales de la salud en momentos de epidemias es el temor 15,37-39. En nuestro estudio, el 84% de los médicos generales informó temor al COVID-19.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Maqsoom et al [24] also showed in their study that psychosocial factors affect the productivity and health of construction workers. Ibrahim et al also conducted a study on the relationship between psychosocial factors and health care productivity in 2019, which showed that psychosocial factors affect more than 50% of health care productivity [25]. Cho et al [26] showed in their study that psychosocial factors in the workplace can negatively affect productivity and mental and physical health of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo do Paquistão verificou que o estresse foi um dos principais fatores que interferiram na qualidade da assistência (49) . Ibrahim et al também observaram que os estressores psicossociais associados ao trabalho prejudicaram em mais de 50% a produtividade dos profissionais (50) .…”
Section: Complicaçõesunclassified